Interpreting the Dynamics of Trust and Control in Management Accounting within Collaborative Work Settings - Rely, Gilbert; Marjono, Marjono; Sudana , I Made; Harahap , Subur (Dinasti Publisher, 2026)
The dynamics between trust and control mechanisms in management accounting are becoming a strategic issue in modern organizations that rely on cross-functional collaboration, especially in the manufacturing sector that demands intensive coordination and accuracy of information between units. Tension and alignment between trust and control have the potential to determine the effectiveness of collaboration, but empirical evidence in the Indonesian context is still limited. This study aims to analyze the influence of trust and management control systems on collaborative performance in a collaborative work environment, as well as examine the role of the interaction between the two in strengthening or weakening the effectiveness of cooperation. As a complement to the quantitative approach, this study applies a comparative case study to several manufacturing companies in West Java to capture the variation in trust and control practices in the dynamics of collaboration between divisions. Using a survey of 150 employees from various departments and companies, data was collected through a structured questionnaire and analyzed using multiple linear regression and interaction tests to identify direct relationships and moderation effects between variables. The results showed that trust had a strong positive influence on collaborative performance, while formal control mechanisms provided a more moderate but still significant positive influence. In addition, participatory designed controls have been shown to strengthen the relationship between trust and collaborative performance, confirming that the two mechanisms can function complementarily. These findings conclude that the integration of trust and control based on management accounting is an important prerequisite for the effectiveness of collaboration in the modern organizational environment, as well as making a theoretical contribution to the management accounting literature and practical implications for the design of control systems that support interdivisional coordination.